Passive Enhancement of Retinol Skin Penetration by Jojoba Oil Measured Using the Skin Parallel Artificial Membrane Permeation Assay (Skin-PAMPA): A Pilot Study - Gruber JV; Terpak N; Massard S; Schwartz A; Bojanowski K (Dove Medical Press, 2023)
James V Gruber,1 Nicole Terpak,2 Sebastien Massard,2 Amber Schwartz,3 Krzysztof Bojanowski4 1Research, Vantage Specialties, Fairfield, NJ, USA; 2Research, Vantage Specialties, Warren, NJ, USA; 3Production, Vantage Specialties, Tucson, AZ, USA; 4Research, Sunny Biodiscovery, Santa Paula, CA, USACorrespondence: James V Gruber, Email Vincent.Gruber@Vantagegrp.comIntroduction: Retinol is known to have positive benefits on the skin including enhancements in barrier function, increased epidermal thickness, reductions in fine lines and wrinkles and reductions in hyperpigmentation. Improved methods to enhance the penetration of retinol are desirable.Methods: A study was conducted to examine if addition of natural jojoba (Simmondsia chinensis) oil might help passively enhance the penetration of retinol through the skin's lipid barrier. The model used to examine the passive penetration of the retinol is the skin parallel artificial membrane permeation assay (Skin-PAMPA). In this study, three formulations were examined. The formulations included two control blends: a moisturizing emulsion without retinol and the same product containing 1.0% retinol without jojoba oil. The remaining formulation contained similar concentrations of retinol with 10% jojoba oil. The studies were conducted by applying the products to the Skin-PAMPA models at 37°C/5% CO2 for 16 hours and then extraction of the acceptor reservoir with cyclohexane (ratio 1:5 acceptor fluid to cyclohexane). The resulting acceptor reservoir cyclohexane solutions were analyzed for retinol by High Performance Liquid Chromatography (HPLC).Results: The formulations without retinol showed no indications of retinol penetration by HPLC. The control formulation with 1.0% retinol demonstrated that retinol had permeated the membrane in the 16-hour timeframe with a measured Area Under the Curve (AUC) of 7 units. Analysis of the formulation containing 1.0% retinol and 10% jojoba oil indicated retinol had permeated with a AUC of 285 units, a nearly 40-fold increase in active retinol permeation.Discussion: The ability for jojoba oil to directly act to help skin permeation of a key skin care active like retinol has not been previously demonstrated. This potential for jojoba oil to enhance passive skin penetration of critical skin actives, like retinol, can help to improve the performance of skin care products employing active topical ingredients.Keywords: skin permeation, retinoids, HPLC, lipid barrier, Simmondsia chinensis oil